The Hotel Strategy during the Pandemic of COVID-19: The Case of Secondary Cities - Ringkar Situmorang; Septi Fahmi Choirisa; Amit Mehrotra (Conference Series, 2021)
The pandemic of COVID-19 has given a disaster to the business industry. Many businesses have to concede that they have to suffer financially because of this situation. One of those businesses that suffered is the hotel business. Many hotel companies have to find a strategy to ensure their relationship between the main city (head office) and secondary cities (branch office) working seamlessly to mitigate this crisis. The primary purpose of this study is to investigate how the hotel industry is handling the challenges during pandemic COVID-19 in the secondary cities. This study adopted qualitative research with 12 semi-structured interviews from various hotel managers in multiple cities. The result showed some discrepancies in the interrelationship between the head office and the branch office in secondary cities, creating uncertainties among them. This study contributed to the crisis management literature in hospitality and tourism industry by exploring the challenges from the pandemic of COVID-19 among cities in Indonesia.